140 A pilot implementation study of saferteens-pc: a violence intervention for adolescent primary care patients. (5th May 2020) - Kotov, Meredith; Tzilos, Golfo; Eisman, Andria; Sigel, Eric; Bourque, Carrie; Carter, Patrick; Cunningham, Rebecca; Walton, Maureen
Abstract : Statement of Purpose: Youth violence is a leading cause of morbidity and mortality. Adolescent primary care visits provide an opportunity for violence screening and delivery of interventions, which are not typically offered in this setting. Thus, we examined implementation of an evidenced-based behavioral intervention (SafeERteens) in primary care. Methods/Approach: Adolescents (ages 14–18) reporting past year aggression on a screening survey were eligible. A quasi-experimental deign was used, enrolling a comparison sample (e.g., resource brochure) and an intervention sample, which consisted of clinic staff delivering a 30-minute Motivational Interviewing-based brief intervention, followed by automatic text message boosters over 8 weeks. Follow-up surveys were complete at 3-months. Results: Overall, about half (50.0%; 56.6%) of youth screened positive, with 110 enrolled (n=49 comparison; n= 61 intervention). Intervention delivery characteristics varied by clinic, including completion (75.9%; 62.5%), modality (100% telehealth; 60% telehealth/40% in-person), and enrollment in text messages (81.8%; 55.0%). In analyses comparing relative changes over time (using an intent-to-treat approach), the intervention group showed significantly greater reductions in severe peer aggression (p<0.05), anxiety (p<0.05) and substance use consequences (p<0.05) relative to the comparison group. Other outcomes examined were in the expected direction, with greater reductions in intervention vs comparison groups in peer victimization, substance use, intention to avoid fighting, and depression (all p's<0.10). Participant and staff feedback was positive, identifying challenges to long-term implementation. Conclusions: Findings support the feasibility and preliminary effectiveness of delivering violence interventions in primary care, with key lessons learned informing future translation of behavioral interventions into routine care in primary care. Significance/Contribution to Injury and Violence Prevention: Primary care is a useful setting to identify adolescents involved with violence, and deliver interventions, which could reduce injury and improve health outcomes.